SYNERGY EFFECT OF INNOVATION AS AN ENABLER OF THE FIRM PERFORMANCE: SME’S CULINARY INDUSTRY - Ma'ruf, Ma'ruf; Lita, Ratni Prima; Meuthia, Meuthia; Syafrida, M. Fajar (TRIKONOMIKA, 2025)
This study investigates the relationship between organizational innovation, marketing innovation, and product innovation with company performance in the food industry in West Sumatra Province, Indonesia. The population of this study consists of small food souvenir businesses operating in the region. Data were collected from 150 respondents using non-probability sampling techniques, precisely the purposive sampling method, and analyzed using the structural equation modelling method and SmartPLS 3.0 software. The study's results revealed that organizational innovation and product innovation did not positively and significantly impact company performance. However, marketing innovation positively and significantly impacted product innovation and company performance. However, marketing innovation did not moderate the relationship between product innovation and company performance in the food industry. The results imply that it is important for business actors to strengthen organizational and human resource development and product development through high-quality research and development that is more impactful on performance.